2016
DOI: 10.1597/14-259
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Prevalence of Cleft Lip/Palate in Southern Thailand

Abstract: The prevalence of oral clefts was 1.44 per 1000 live births, with 15% of cases having an associated congenital anomaly or a recognized syndrome. Increased maternal age was associated with a higher prevalence of syndromic cleft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…But the most common forms of syndromic oral clefts are Van der Woude syndrome and 22q11.2 deletion syndrome ( Burg et al, 2016 ). In this study many patients with syndromic OFCs showed some of these conditions, as observed in previously reports ( Jaruratanasirikul et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…But the most common forms of syndromic oral clefts are Van der Woude syndrome and 22q11.2 deletion syndrome ( Burg et al, 2016 ). In this study many patients with syndromic OFCs showed some of these conditions, as observed in previously reports ( Jaruratanasirikul et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…The central region has the particularity of having mainly cases with low severity (PC) or medium (CL), while the southeast region has the most severe cases (CLP), accentuating CLPu over CLPb, as reported in the literature. [32][33][34] Then, Bogotá has been reported as the most important reference center for health care in the country, the CL/P population migrates internally in search of care and better technology.…”
Section: Discussionmentioning
confidence: 99%
“…7,21 In Saudi Arabia, a prevalence at birth rate of 0.65 per 1000 live births was reported 22 ; in Iran, 1.9 per 1000 live births 23 ; and in Thailand, 1.44 per 1000 live births. 24 The variability in estimates may be due to multiple causes, including different methods, and racial and environmental differences in populations. 20 Importantly, studies using nationally reported data come from countries with more advanced surveillance and coverage systems.…”
Section: Discussionmentioning
confidence: 99%